2020
DOI: 10.3389/fmicb.2020.00934
|View full text |Cite
|
Sign up to set email alerts
|

An Association of an eBURST Group With Triazole Resistance of Candida tropicalis Blood Isolates

Abstract: Candidemia, a bloodstream infection caused by genus Candida, has a high mortality rate. Candida albicans was previously reported to be the most common causative species among candidemia patients. However, during the past 10 years in Thailand, Candida tropicalis has been recovered from blood more frequently than C. albicans. The cause of this shift in the prevalence of Candida spp. remains unexplored. We conducted in vitro virulence studies and antifungal susceptibility profiles of 48 C. tropicalis blood isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
(64 reference statements)
2
13
0
Order By: Relevance
“…C. tropicalis was the most common cause of candidemia, followed by C. albicans , C. glabrata , and C. parapsilosis . This is consistent with previous studies, including a report that C. tropicalis was the most frequent species isolated from blood samples in the same geographic area of Thailand [ 12 , 13 , 14 , 15 ]. Although several studies identified C. albicans as the most common fungus isolated from blood samples, more recent studies reported a decreasing frequency of C. albicans -associated candidemia and an increasing frequency of candidemia associated with NAC [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…C. tropicalis was the most common cause of candidemia, followed by C. albicans , C. glabrata , and C. parapsilosis . This is consistent with previous studies, including a report that C. tropicalis was the most frequent species isolated from blood samples in the same geographic area of Thailand [ 12 , 13 , 14 , 15 ]. Although several studies identified C. albicans as the most common fungus isolated from blood samples, more recent studies reported a decreasing frequency of C. albicans -associated candidemia and an increasing frequency of candidemia associated with NAC [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…MLST can clarify the genetic diversity among isolates and characterize the fluconazole susceptibility pattern [ 46 ]. The genetic diversity observed in this study was comparable to that of a previous study in Thailand [ 12 ] but higher than that in other countries [ 47 ]. CC1, a major cluster associated with azole resistance in this study, is a large fluconazole-non-susceptible group found in Taiwan and China [ 46 , 48 ].…”
Section: Discussionsupporting
confidence: 85%
“…The proportion of C. tropicalis among Candida species causing candidaemia are relatively high in tropical Asia and Latin America compared to other continents [2,3]. Azole-resistant C. tropicalis clinical isolates have emerged worldwide [4][5][6][7][8][9][10][11]. This has become particularly problematic in the Asia-Pacific region since 2010 [4,5,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the association between azole use and the emergence of ANS C. tropicalis isolates, we analyzed the clinical history of respective patients (20/127; 15.7%) and found that 50% of them were azole-naïve, which is similar to the results obtained for patients infected with Candida parapsilosis ( Tóth et al, 2019 ) and C. auris ( Jeffery-Smith et al, 2018 ). Recent studies from Iran ( Arastehfar et al, 2020a ), Taiwan ( Chen et al, 2019 ), and Japan ( Chong et al, 2012 ) have reported the same phenomenon, which could be the driving force behind the replacement of C. albicans as the first leading cause of candidemia with C. tropicalis documented in Taiwan ( Tulyaprawat et al, 2020 ). We also found an association between fluconazole resistance and genotypes, which may account for the dramatic increase in the number and persistence of ANS isolates in clinical settings since the previous candidemia study in Turkey ( Arikan-Akdagli et al, 2019 ), hypothetically because azole-resistant isolates may possess a higher mutagenesis potential allowing them to thrive in conditions when fluconazole is heavily used ( Healey et al, 2016 ).…”
Section: Discussionmentioning
confidence: 74%